Systematic chemoenzymatic synthesis of O-sulfated sialyl Lewis x antigens. Issue 4 (25th January 2016) - Santra, Abhishek; Yu, Hai; Tasnima, Nova; Muthana, Musleh M.; Li, Yanhong; Zeng, Jie; Kenyon, Nicholas J.; Louie, Angelique Y.; Chen, Xi
Abstract : O -Sulfated sialyl Lewis x antigens containing different sialic acid forms were chemoenzymatically synthesized using a bacterial sialyltransferase mutant. Abstract : O -Sulfated sialyl Lewis x antigens play important roles in nature. However, due to their structural complexity, they are not readily accessible by either chemical or enzymatic synthetic processes. Taking advantage of a bacterial sialyltransferase mutant that can catalyze the transfer of different sialic acid forms from the corresponding sugar nucleotide donors to Lewis x antigens, which are fucosylated glycans, as well as an efficient one-pot multienzyme (OPME) sialylation system, O -sulfated sialyl Lewis x antigens containing different sialic acid forms and O -sulfation at different locations were systematically synthesized by chemoenzymatic methods.